2023
DOI: 10.1021/acs.jpcb.2c07992
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Dynamics of Aqueous Halides before and after Photoionization

Abstract: Electron transfer reactions can be strongly influenced by solvent dynamics. We study the photoionization of halides in water as a model system for such reactions. There are no internal nuclear degrees of freedom in the solute, allowing the dynamics of the solvent to be uniquely identified. We simulate the equilibrium solvent dynamics for Cl–, Br–, I–, and their respective neutral atoms in water, comparing quantum mechanical/molecular mechanical (QM/MM) and classical molecular dynamics (MD) methods. On the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 125 publications
(280 reference statements)
0
6
0
Order By: Relevance
“…While e aq – is rather transparent to X-rays, using computations of the K-edge X-ray absorption spectra (XAS), Li et al recently showed that X-rays could be used to probe the presence of the cavity around e aq – . They suggested using time-resolved X-ray absorption spectroscopy (trXAS) to track changes in the solvation structure of e aq – exploiting the high structural sensitivity of XAS. , X-rays have already demonstrated their exceptional suitability for uncovering local transient structures in liquid water. , But so far, experimental applications of X-ray spectroscopy to the solvated electron and its solvation shell remain absent. In this article, we report the most direct evidence of cavity formation with the help of trXAS.…”
Section: Introductionmentioning
confidence: 99%
“…While e aq – is rather transparent to X-rays, using computations of the K-edge X-ray absorption spectra (XAS), Li et al recently showed that X-rays could be used to probe the presence of the cavity around e aq – . They suggested using time-resolved X-ray absorption spectroscopy (trXAS) to track changes in the solvation structure of e aq – exploiting the high structural sensitivity of XAS. , X-rays have already demonstrated their exceptional suitability for uncovering local transient structures in liquid water. , But so far, experimental applications of X-ray spectroscopy to the solvated electron and its solvation shell remain absent. In this article, we report the most direct evidence of cavity formation with the help of trXAS.…”
Section: Introductionmentioning
confidence: 99%
“…28−32 Changes in solvation shells and liquid structure following an optical actinic pulse 33−42 have been tracked and analyzed using molecular dynamics. 43,44 The ultrafast X-ray probe provides an adequate temporal resolution of the structural dynamics. 31,45−48 In this study, we combine local SXRS excitation on a solute molecule with an XRD probe of the structural solvent response.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This wavepacket can involve a large number of valence excited states covered by the large bandwidth of X-ray pulses. In another development, it is now possible to obtain diffraction images of noncrystalline molecular samples in the gas and liquid phases by time-resolved X-ray diffraction (XRD). Changes in solvation shells and liquid structure following an optical actinic pulse have been tracked and analyzed using molecular dynamics. , The ultrafast X-ray probe provides an adequate temporal resolution of the structural dynamics. , …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many investigations have been dedicated to study aqueous solutions of halide ions and to provide a molecular level understanding of halide–water interactions . A plethora of different techniques have been adopted to characterize the hydration properties of halides, including classical molecular dynamics (MD) and Monte Carlo simulations, QM/MM simulations, ab initio simulations, ,,, Raman and IR spectroscopies, X-ray absorption spectroscopy, ,,, and neutron and X-ray diffraction . Nevertheless, the picture of halide solvation shell structure emerging from such works is inhomogeneous, and first shell coordination numbers and distances reported in the literature are very scattered .…”
Section: Introductionmentioning
confidence: 99%